PENGEMBANGAN KAPABILITAS EKONOMI DENGAN DIFERENSIASI PRODUK SUSU DI DESA CIBODAS KECAMATAN LEMBANG KAB. BANDUNG BARAT (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
This service is motivated by the problem of the low income of the people of Cibodas Village. One of the efforts to increase people's income is to increase the added value of cow's milk as one of the superior products of Cibodas Village into several dairy products that have higher added value. Increased value added by differentiation of dairy products, will increase people's income. However, most people do not have the skills to process dairy products. For this purpose, people need skills to process whole milk into other processed products (differentiate) and develop differentiated products by branding and packaging dairy products to be more informative and attractive. Based on this, this service activity aims to provide community assistance through milk processing training activities, providing product brands and packaging dairy products. The method of service carried out is by direct participation with assistance to the wives of cow breeders who are members of the PKK Karya Ibu Desa Cibodas Lembang who are partners in this research. The result of this service is an increase in partners' skills in making dairy products, determining brands, packaging, producing ready-to-sell dairy product differentiation and projecting partners' business profit and loss.